Building Resilient Food Systems: Government Community Collaboration in Flood Mitigation - Anthony Steven; Iriani Atrika; Doris Febriyanti; Siti Zubaidah (Government & Resilience, 2025)
Palembang, one of Indonesia’s major urban centers, is increasingly affected by recurrent flooding that severely disrupts local food systems. As a low-lying delta city intersected by the Musi River, Palembang faces compounded challenges due to rapid urban expansion, poor drainage infrastructure, and climate-induced rainfall variability. These factors contribute not only to physical flooding but also to food insecurity, particularly among poor urban communities who depend on fragile food supply chains and informal markets. This study investigates how collaborative governance between local authorities and community stakeholders in Palembang can contribute to building resilient food systems amid recurrent flood risks. Using a case study approach, it analyzes local policy responses, community-led initiatives such as floating vegetable gardens, and urban farming on flood-resilient land. The findings indicate that while municipal disaster management agencies provide early warning and evacuation support, food access and distribution during floods are primarily sustained by grassroots networks and community-organized food banks. The paper emphasizes the importance of institutionalized support for community-based adaptation, integrated spatial planning utilizing flood-risk mapping, and policy frameworks that acknowledge food as a vital component of urban disaster preparedness. Palembang serves as a microcosm for examining the broader implications of decentralized disaster governance and food resilience in rapidly urbanizing flood-prone cities.